If f(x)= 3cos(2x) + sin(2x)f(x)=3cos(2x)+sin(2x), how can I find f'(x)?

1 Answer
Jan 26, 2015

First of all, let's remark that the derivative of a sum is the sum of the derivatives, and so we can study the function one addend at the time.

In both cases, anyway, you'll need the chain rule, a formula which tells us how to derivate composite function.

By composite function, we mean a function which evaluates another function, as when we write f(g(x)). The derivative of such a function is f'(g(x)) g'(x).

Studying the first addend, we have that f(x)=\cos(x), and g(x)=2x.

Since the derivative of \cos(x) is -\sin(x), and the derivative of 2x is 2, we have that
d/dx 3\cos(2x) = 3 d/dx \cos(2x) = 3(-\sin(2x) \cdot 2)

Similar steps lead us to say that
d/dx \sin(2x) = \cos(2x)\cdot 2. Adding the two, one has that

d/dx 3cos(2x)+sin(2x) = 2(\cos(2x)-3\sin(2x))